Molecular ABO blood group genotyping in the Indonesian Minangkabau population - Hidayat, Taufik; Ishar, Seri Mirianti; Din, Rus Dina Rus; Haron, Nor Hafidza; Md Isa, Nur Mahiza; Hamzah, Noor Hazfalinda (Mary Ann Liebert, 2025)
Objectives: Investigating the molecular ABO blood group genotyping in specific populations helps improve our understanding of population genetics and its forensic applications. This study aimed to determine the genotypes and allele frequencies of ABO blood groups in the Minangkabau population. Materials and Methods: Blood samples were obtained from 200 participants (74 males and 126 females) using consecutive sampling. Only healthy, unrelated Minangkabau individuals with no history of interracial marriage of up to three generations were included. The polymerase chain reaction-restriction fragment length polymorphism technique was employed to amplify segments of the transferase gene, specifically nucleotide 261 in exon 6 and nucleotide 703 in exon 7 of the ABO gene locus, using the restriction enzymes Kpn1 and Alu1. Results: Phenotypic distribution revealed that 46.5% of participants were type A, 33% type B, 16% type O, and 4.5% type AB. The genotypes identified were 4.5% AA, 42% AO, 1.5% BB, 31.5% BO, 4.5% AB, and 16% OO. The gene frequencies calculated were 0.4 for the Io allele, 0.39 for the Ia allele, and 0.21 for the Ib allele. Conclusions: These findings provide valuable insights into the genetic structure of the Minangkabau population and contribute to the understanding of ABO allele distributions in Southeast Asia, with potential applications in population genetics and forensic science.